Preliminary study of the oral mycobiome of children with and without dental caries. Issue 1 (1st January 2019) - Fechney, Jacquelyn M.; Browne, Gina V.; Prabhu, Neeta; Irinyi, Laszlo; Meyer, Wieland; Hughes, Toby; Bockmann, Michelle; Townsend, Grant; Salehi, Hanieh; Adler, Christina J.
ABSTRACT: Children's oral health is in a dire state, with dental decay (caries) being one of the most common chronic diseases. While the role of bacteria in the oral microbiome and dental caries is established, the contribution of fungi is relatively unknown. We assessed the oral mycobiome in childhood ( n = 17), to determine if the composition of fungi varies between children with and without caries. Oral mycobiome composition was assessed by using Illumina MiSeq to sequence the ITS2 region, which was amplified from dental plaque. This revealed that the oral mycobiome in the investigated children contained 46 fungal species.  Candida albicans  was the most abundant species and was ubiquitous in all samples, indicating this species may not be involved in caries development as previously suggested. While the overall diversity of fungi was similar, independent of caries status ( p > 0.05), we found caries influenced the abundance of specific fungi. Children without caries had a significantly higher abundance of 17 species compared to children with caries, which had three enriched species ( p < 0.001). While the differentially abundant species between health and caries may be specific to an Australian population, our findings indicate the mycobiome plays a role in oral health.